Production and validation of the short film Pés que te quero®: educational technology for people with diabetes - Luciana Gomes Catunda Menezes; Maria Vilani Cavalcante Guedes; Sherida Karinini Paz de Oliveira; Roseanne Montargil Rocha; Ana Karina Bezerra Pinheiro; Lúcia de Fátima da Silva; Denizielle de Jesus Moreira Moura; Manuela de Mendonça Figueirêdo Coelho (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To describe the production and validation of short film type educational technology for the prevention of diabetic foot ulcers. Methods: A methodological study focused on the validation of a short film. The construction of the film was carried out in three stages: pre-production, production, and post-production. Thirty-seven evaluators undertook the internal validation, divided into two groups of 31 proficient nurses and six from the communication area. Fifteen people with diabetes mellitus performed the external validation. Result: The nursing proficient validated the script with a total content validity index of 0.95, with internal reliability of 0.849 conferred by Cronbach's Alpha. Communication specialists validated with a content validity index of 0.97; and target audience with 0.95 (clarity) and 0.97 (relevance). Conclusion: The study showed that the short film is a valid and reliable educational technology to promote foot care to people with diabetes mellitus.